Hadith About Social Concern - Agna Rahmat Maulana; Uus Husni Hoer; Siti Fitria Firmansyah; Zahron Nafisah (Taqriri: Journal of Al-Hadith Science Studies, 2025)
The Hadith about social care illustrates the teaching of Islam that emphasize the importance of solidarity, emphaty, and a sense of responsibility toward others. Prophet Muhammad (peace be upon him) emphasized that a believer is part of a community that cares for one another, as he said :”The example of the believers in their affecation, mercy, and compassion for each other is that of a body; when any limb aches the whole body reacts with sleeplessness and fever”(Narrated by Bukhari and Muslim). This hadith teaches that muslims must be sensitive to the needs and difficulties of others, including helping those who are underprivileged, marginalized, or afflicted by calamities. The social care emphasized in this hadith forms the foundation for creating a harmonious and prosperous society where the values of brotherhood   and humanity are prioritized.